Children’s Eating Behavior Questionnaire Correlated with Body Compositions of Thai Children and Adolescents with Obesity: A Pilot Study - Ekkarit Panichsillaphakit; Yuda Chongpison; Puthita Saengpanit; Tanisa Kwanbunbumpen; Jaraspong Uaariyapanichkul; Sirinuch Chomtho; Chitsanu Pancharoen; Chonnikant Visuthranukul (Journal of Nutrition and Metabolism)
Introduction. Obesity is a major threat to public health. Eating behavior and dietary intake of especially high energy-dense food with low nutrients contribute to the current epidemic of childhood obesity. However, the relationship between eating behavior and body composition has yet to be examined in Thai children and adolescents with obesity. We assessed the association between children’s eating behaviors and their body composition in prerandomized patients who participated in the randomized trial titled “Impact of Dietary Fiber as Prebiotics on Intestinal Microbiota in Obese Thai Children”. Methods. During the prerandomization process, a cross-sectional study was conducted. We recruited children and adolescents aged 7 to 15 years from Bangkok, Thailand. Eating behaviors were assessed by the Children’s Eating Behavior Questionnaire (CEBQ), which is a parent or self-reported research instrument conducted by face-to-face interviews. Body mass index (BMI), BMI-for-age Z-score, waist and hip circumferences, and body compositions were assessed. Pearson’s correlation coefficients were used to assess associations between the study variables. Results. Ninety-seven Thai children and adolescents with obesity participated in the study; 59 (61%) were male. Median [IQR] of age and BMI z-score were 10.5 [9.0, 12.2] years and 3.0 [2.6, 3.7], respectively. Subscale for Enjoyment of Food had the highest score. There were no associations between eating behaviors and BMI z-score. However, Emotional Overeating was associated with fat-free mass index (correlation coefficient = 0.24, p=0.02) and girls with obesity had lower scores in “Slowness in Eating” compared to boys [mean 2.1 versus 1.8, 95% CI: (−0.06, −0.01), p=0.04]. Conclusion. Among Thai children and adolescents with obesity, the difference in multidimensional eating behavior might be affected by fat-free mass. Additional study with a larger sample size needed to explore underlying mechanisms and findings can be used to develop future behavior modification program.